Proteomic insights into short neurotoxin-driven, highly neurotoxic venom of Philippine cobra (Naja philippinensis) and toxicity correlation of cobra envenomation in Asia - Tan, Choo Hock; Wong, Kin Ying; Chong, Ho Phin; Tan, Nget Hong; Tan, Kae Yi (Elsevier, 2019)
The Philippine cobra, Naja philippinensis, is a WHO Category 1 venomous snake of medical importance responsible for fatal envenomation in the northern Philippines. To elucidate the venom proteome and pathophysiology of envenomation, N. philippinensis venom proteins were decomplexed with reverse-phase high-performance liquid chromatography, and protein fractions were subsequently digested with trypsin, followed by nano-liquid chromatography-tandem mass spectrometry analysis and data mining. Three-finger toxins (3FTX, 66.64% of total venom proteins) and phospholipases A2 (PLA2, 22.88%) constitute the main bulk of venom proteome. Other proteins are present at low abundances (<4% each); these include metalloproteinase, serine protease, cobra venom factor, cysteine-rich secretory protein, vespryn, phosphodiesterase, 5′ nucleotidase and nerve growth factor. In the three-finger toxin family, the alpha-neurotoxins comprise solely short neurotoxins (SNTX, 44.55%), supporting that SNTX is the principal toxin responsible for neuromuscular paralysis and lethality reported in clinical envenomation. Cytotoxins (CTX) are the second most abundant 3FTX proteins in the venom (21.31%). The presence of CTX correlates with the venom cytotoxic effect, which is more prominent in murine cells than in human cells. From the practical standpoint, SNTX-driven neuromuscular paralysis is significant in N. philippinensis envenomation. Antivenom production and treatment should be tailored accordingly to ensure effective neutralization of SNTX. Biological significance: The venom proteome of Naja philippinensis, the Philippine cobra, is unravelled for the first time. Approximately half the protein bulk of the venom is made up of short neurotoxins (44.55% of the total venom proteins). As the only alpha-neurotoxins present in the venom, short neurotoxins are the causative toxins of the post-synaptic blockade and fast-onset neuromuscular paralysis in N. philippinensis envenomation. A substantial amount of cytotoxins (21.31%) was also detected in N. philippinensis venom, supporting that the venom can be cytotoxic although the effect is much weaker in human cells compared to murine cells. The finding is consistent with the low incidence of local tissue necrosis in N. philippinensis envenomation, although this does not negate the need for monitoring and care of bite wound in the patients. © 2019 Elsevier B.V.